Activating the Partnership between King Saud University and King Salman Social Center in Light of International Experiences - Alnashar, Sahar bint Khalid; Alhasef, Moonerah Mesfer; Altameme, Nada Abdullah; Almubairik, Haifa Fahad (Journal of Educational and Psychological Sciences, 2021)
This study aims to identify the reality of community partnership between King Saud University and King Salman Social Center from the perspective of the center staff, and it sought to explore the barriers of this partnership. It also aims to identify whether there are statically significant differences attributed to the years of experience variable and to get a proper suggested proposal to activate the partnership in the light of international experience. To achieve these objectives, the researchers used the survey descriptive approach and a questionnaire. The study community consisted of the staff of King Salman Social Center in Riyadh city, in the year (1441/1442 H), who is 80 female and male employees. The study sample was represented in a random sample of (41) of the center staff. The study concluded a group of results: The study sample agrees with “medium degree” on “the reality of partnership between King Saud University and King Salman Social Center from the perspective of the center staff”, Results also showed that the sample agrees with “medium degree” on “barriers of the partnership between King Saud University and King Salman Social Center from the perspective of the center staff”, and that there are statically significant differences within means of study sample responses on the reality of partnership according to years of experience. Differences came in favor of those with three years of experience and less.